Teaching Home Reading in the German Language Classes Using Information and Communication Technologies (from the Experience of Working in a Non-Linguistic Institution) - E. A. Zimina (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The specifics of the teaching of home reading in a non-linguistic university at the junior Bachelor’s programs (German as the main language) using information and communication technologies are characterized. It is noted that the classes within the framework of this course are aimed at the formation of a communicative foreign speaking competence. The relevance of the study is due to the importance of development of monologic speech and the primary skills of conducting discussions on the problems of reading texts in international students at early stages of studies. Attention is also given to the students mastering the elements of text analysis. The author dwells on the principles of selecting literature for home reading (authenticity, accessibility, relevance). The review of works and didactic materials which are involved at the organization of classes on home reading of 1-2 year Bachelor’s degree students of non-language high school is presented. Particular attention is paid to the use of information and communication technologies in teaching for the effectiveness of the learning process of foreign language and the development of foreign communicative competence. Examples are provided on how innovative approaches to the organization of classroom and independent work on the home reading of Bachelor’s degree students used at the MGIMO, the Ministry of Foreign Affairs of Russia, who study German as the main language.